Pengaruh Harga dan Promosi Terhadap Peningkatan Volume Penjualan Kartu Perdana Indosat Ooredoo Pada PT. Mitra Bisnis Seluler Cabang Lahat - Hestin Hestin (Ekonomika, 2021)
The purpose of this study was to determine the effect of price on an increase in sales volume, to determine the effect of promotion on an increase in sales volume and to determine the effect of selling prices and promotions on an increase in sales volume of Indosat Ooredoo starter packs at PT. Lahat Branch Cellular Business Partner. The data collection technique used is the documentation technique. The results showed that there was an effect of price on sales volume, there was an effect of promotion on the increase in sales volume of Indosat Ooredoo starter packs at PT. Cellular Business Partners. Lahat branch, and there is a significant influence between price and promotion on the increase in sales volume of Indosat Ooredoo starter packs at PT. Cellular Business Partners. Lahat Branch. Based on the results of multiple linear regression, it is known that the coefficient value of the f test results is 3.135 with a significant level of 5%. The price variable is more dominant in partially influencing the increase in sales volume.